Auditor Experience and the Timeliness of Litigation Loss Contingency Disclosures* - Chen, Feng; Hou, Yu; Richardson, Gordon; Ye, Minlei (Contemporary Accounting Research, 2018)
ABSTRACT This paper hypothesizes and finds that firms audited by city‐industry specialists have more timely disclosures of contingent losses from litigation when there is no news coverage relating to the legal case prior to management disclosures. A closer examination reveals that this result is explained by the specialist auditors’ prior experience auditing clients in the same office and industry who are involved with litigation. In our setting, disclosures of litigation‐related contingent losses, we identify two kinds of knowledge generated from experience: industry knowledge and litigation knowledge. Industry knowledge helps auditors detect and correct poor implementation of guidance for litigation loss contingency disclosures. Auditors gain litigation knowledge from auditing clients in a given office and industry with previous involvement as defendants. Thus, the two types of knowledge interact in their effects on reporting outcomes.